Stuyvesant bound : an essay on loss across time - Merwick, Donna (Early American studies., 2013)
This book is a compelling reassessment of the last Director-General of New Netherland. The author employs a multidisciplinary approach to examine the layers of culture within which Peter Stuyvesant forged his career and performed his identity.